The nature of excitons in PPDT2FBT:PCBM solar cells: Role played by PCBM. (10th November 2022) - Sahoo, Subhamoy; Barah, Dhruvajyoti; Kumar S, Dinesh; Xavier, Nithin; Dutta, Soumya; Ray, Debdutta; Bhattacharyya, Jayeeta
Abstract: In organic semiconductor-based bulk heterojunction solar cells, the presence of an acceptor increases the formation of charge-transfer (CT) excitons, thereby leading to higher exciton dissociation probabilities. In this work we used steady-state electroabsorption (EA) measurements to probe the change in the nature of excitons as the blend composition of the solar cell active layer material was varied. We investigated blends of poly[(2, 5-bis(2-hexyldecyloxy)phenylene)-alt-(5, 6-difluoro-4, 7-di(thiophen-2-yl)benzo[c]-[1, 2, 5]thiadiazole)] (PPDT2FBT) and (6, 6)-phenyl C71 butyric acid methyl ester (PCBM). Analysis of the EA spectra showed that in the presence of a fullerene-based acceptor, like PCBM, CT characteristics of the excitons were modified, though no new CT signature was observed in the blend. Enhancement in the CT characteristics in the blend was reflected in photoluminescence (PL) measurements of the blends, where PL quenching of ∼63% was observed for 1% PCBM. The quenching reaches saturation at about 20% PCBM. However, efficiency of the device increased with a PCBM percentage beyond 20%. Maximum efficiency was obtained for the blend with 50% PCBM, among the blend compositions studied in this work, indicating the optimum concentration of PCBM for best power conversion efficiency to be around that value. When we compared the experimental results with simulations, the variation of the device efficiency with PCBM percentage was shown to arise from multiple factors, such as an increase in the polarizability and dipole moment of excitons, and the efficiency of the carrier collection from the bulk of the active layer.